Electrophoretic deposition of chitosan/Bioglass® and chitosan/Bioglass®/TiO2 composite coatings for bioimplants - Clavijo, Silvia (2016)
Electrophoretic deposition (EPD) method has been developed for the fabrication of chitosan/Bioglass and chitosan/Bioglass/TiO2 composite coatings on stainless steel substrates for biomedical applications. Microstructure, thickness, and mechanical properties, such as Vickers microhardness, compressive strength, and elastic modulus were determined. The use of chitosan enabled the co-EPD of Bioglass and TiO2 particles and offered the advantage of room temperature processing typical of EPD. The coating composition was varied by the combination of Bioglass and TiO2 concentrations in the chitosan solutions used for EPD. The cathodic deposition yield was studied at constant voltage for various deposition times. The coatings were microstructurally characterized by scanning electron microscopy (SEM) and energy dispersive spectroscopy(EDS). Homogeneous chitosan/Bioglass coatings on stainless steel substrates were obtained at constant voltage condition using aqueous suspensions based on 0.016 wt% chitosan and 2 wt% Bioglass. The addition of TiO2 nanopowder to the composite coating was confirmed to improve the hardness, Young's modulus and compressive strength of the base chitosan/Bioglass coating.